Legal Protection of Debtor in Credit Settlement with Fiduciary Guarantee - I Gede Raka Ramanda; Made Wiryani; Ni Luh Mahendrawati (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2021)
This research is based on the provisions of law No. 42 of 1999 on fiduciary, in particular in article 34, and the provisions of article 27 paragraph 3 regulation of the Financial Services Authority No. 33/POJK. 03/2018. There is a conflict of norms between debtors and creditors. The purpose of this study is to find out the legal consequences for debtors who have been voluntarily submitted to the creditor for a voluntary warranty and to find out the legal protection of a debtor who is in good faith hand over a fiduciary guarantee. The theory used in analyzing data is the theory of the Norms (Stufenbau Theorie), the theory of legal certainty and the legal protection theory. Meanwhile, the method used is normative research with a statutory approach. The result of this study showed that Financial Services Authority Regulation Number 33 /Pojk.03/2018 Regarding Quality of Earning Assets and Formation of Allowance for Earning Assets of Rural Credit Banks, regulating the issue of Collateral Foreclosed can be overridden or become not valid, or at least a material test by the Supreme Court. If violated, it results in being null and void. Furthermore, based on legal protection theory, that Article 15 paragraph (2) of Law Number 42 Year 1999 does not provide legal certainty and justice for debtors.